The official guide to the TOEFL test. - Educational Testing Service (New York : McGraw-Hill, 2012)
A preparation guide for the TOEFL Internet-based Test that provides practice questions and essay topics, and also features analyzed multiple-choice questions, scoring information, raters' commentary, and a CD-ROM with three full-length practice tests.
System requirements not stated.
Professional
Professional
Keywords: English language -- Textbooks for foreign speakers; English language -- Examinations -- Study guides; Test of English as a Foreign Language -- Study guides; English as a second language; English language -- Examinations -- Study guides; Test of English as a Foreign Language -- Study guides